Prevention of ACL injuries in female athletes through early intervention - Whittle, R. C.; Crow, B. (The Sport Journal, 2009)
Abstract With respect to physical education, increased participation in sport equals success. One of the main goals of physical educators is to enable individuals to become proficient in lifelong activities. Hopefully, this proficiency will lead to a healthier and more fulfilling life. Beginning with Title IX and continuing over the last two decades, there has been an explosion of youth sports opportunities. As children have begun to participate in sports programs at earlier ages, parents have started feeling pressure to enroll their children in similar programs in order for them to remain competitive. As a result, children become increasingly proficient at their respective sports at earlier ages. This proficiency, while benefiting the respective sport, is not without its consequences. One of the most notable consequences of increased participation in sports at an earlier age is in the area of sports injuries (Rentrom, 2008).